The EFL Students’ Perceptions of AI Writing Tools in Academic Writing Skills at Islamic University of Palangka Raya - Suryani, Yeni; Nirwanto, Rahmadi; Qamariah, Zaitun (Journal of English Language and Education, 2025)
The EFL students' difficulties in academic writing, including limitations in grammar, vocabulary, and idea development, necessitate innovative AI-based writing tools solutions. The usage of artificial intelligence (AI)-based writing tools to assist students in producing academic essays is examined in this study. Five English education majors who had completed essay writing classes and had prior experience with AI tools participated in semi-structured interviews as part of a phenomenological qualitative technique to gather data. Students utilize a variety of tools, including ChatGPT, Grammarly, and QuillBot, for brainstorming, grammatical correction, and idea organization, according to the study's findings. In general, they considered AI to be effective in speeding up the writing process, improving language accuracy, and reducing anxiety. However, they emphasized the importance of wise use to avoid sacrificing critical thinking independence. These findings confirm these tools serve as a support, not a substitute, in the development of students' academic writing skills.